Memahami dan Mengatasi Krisis Menjadi Peluang - Peter, Ramot (Humaniora, 2013)
All human must face some crisis in their lives and none can get rid off. Some of them will consider the crisis as a threat that will distress and make their lives insecured. The assumption will happen to the ones who do not comprehend the crisis indeed and can not overcome it. This article discusses: fundamental understanding of crisis, causal factors, types of crisis, and suggestions to avoid distress. This is a kind of library research which sources of information are taken from books, articles, and the writer?s opinions. The purposes of this article are to open someone?s mind and to overcome the crisis. These bring someone to get rid off distress. Having good understanding of crisis and encountering the crisis as a good experience impact to release from distress and to create opportunities.